Electron transport layer precursor and electron transport layer for QLED

The electron transport layer of QLED is prepared using a composition composed of ZnO-based nanoparticles and specific polymers, and the shortcomings of existing ETLs in terms of EQE and stability are solved, achieving more efficient and more stable QLED performance.

CN119896074APending Publication Date: 2025-04-25JOHNSON MATTHEY PLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380067047.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-10-25
Filing Date
2023-10-24
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing electron transport layer (ETL) for QLED has room for improvement in external quantum efficiency (EQE) and is insufficient instability, resulting in a performance decline in a short period of time.

Method used

ETL was prepared by spin coating and annealing processes using compositions containing ZnO-based nanoparticles, polar organic solvents and specific polymers as precursors for the electron transport layer. The polymer of the composition has an average molecular weight Mw from 25000 Da to 1300000 Da, comprising polyvinylpyrrolidone (PVP) and/or poly(ethyloxazoline) (PEO) to improve the structural stability and performance of ETL.

Benefits of technology

The external quantum efficiency (EQE) of QLED is significantly improved and the stability of the composition is enhanced, allowing peak EQE to stabilize for more than three months, with a significant decrease in performance compared to the case where the stabilizer is not used.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119896074A_ABST
    Figure CN119896074A_ABST
Patent Text Reader

Abstract

There is provided a composition comprising ZnO-based nanoparticles, a polar organic solvent, and a polymer wherein the ZnO-based nanoparticles have the formula LixMgyMpZnzO, where 0 lt; xlt; 0.2 part; 0 lt; y + plt; 0.25%; z is equal to (1 to 0.5) x < y > to (1.5) p; and M is an element selected from gallium and / or aluminum; and wherein the polymer comprises polyvinyl pyrrolidone (PVP) and / or poly (ethyl oxazoline) (PEO), the polymer having an average molecular weight Mw of from 25,000 Da to 13,000 Da.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a composition which is a precursor of an electron transport layer; the use of the composition; a method for manufacturing an electron transport layer for QLED; an electron transport layer for QLED; QLED and a visual display unit. Background Art

[0002] Zinc oxide materials are used as electron transport layers (ETLs) in pixels present in next generation display devices, such as so-called QLED (quantum dot light emitting diode) displays, due to their favorable band gap and electron transport properties.

[0003] Pixels in next-generation display devices typically include five or more layers, including a quantum dot light-emitting layer, an electron transport layer, and a hole transport layer. Typically, the thickness of each of the layers is about 50 nanometers to 150 nanometers.

[0004] An important measure of pixel efficiency in a display device is the external quantum efficiency (EQE). EQE can be defined as the ratio of the number of photons emitted by a pixel to the number of electrons that pass through the pixel. The external quantum efficiency can be considered a measure of how efficiently a device converts electrons into photons. The external quantum efficiency is a measure of the entire pixel. However, all other factors being equal, EQE can be used to measure the effectiveness of a zinc oxide ETL.

[0005] The highest EQE recorded for experimental QLEDs is about 20%. For commercial applications, an external quantum efficiency greater than 10% is ideal. Other factors, such as operating lifetime and operating voltage, are also important considerations in the preparation of the electron transport layer.

[0006] Heng Zhang et al. disclosed the use of ZnMgO:PVP (polyvinyl pyrrolidone) inorganic-organic hybrid ETL in an attempt to make an improved ETL for QLEDs in J. Mater. Chem. C (2291-2298) in July 2019. However, there is still a need to further improve ETLs for QLEDs, and in particular, it is desirable to continuously improve the EQE of such QLEDs. Summary of the invention

[0007] One aspect of the present disclosure relates to a composition comprising ZnO-based nanoparticles, a polar organic solvent, and a polymer, wherein the ZnO-based nanoparticles have a formula of Li x Mg y M p Zn zO, wherein 0≤x≤0.2; 0≤y+p≤0.25; z=1-0.5xy-1.5p; and M is an element selected from gallium and / or aluminum; and wherein the polymer comprises polyvinylpyrrolidone (PVP) and / or poly(ethyloxazoline) (PEO), the polymer having an average molecular weight M of 25000Da to 1300000Da w .

[0008] Another aspect of the present disclosure relates to a method of manufacturing an electron transport layer (ETL) for a QLED, the method comprising: providing a composition according to the above aspects; spin coating the composition to provide a spin-coated composition; and annealing the spin-coated composition.

[0009] Another aspect of the present invention relates to use of the composition described in the above aspect in manufacturing an electron transport layer (ETL) for QLED.

[0010] Another aspect of the present disclosure relates to an electron transport layer (ETL) for a QLED, the ETL comprising ZnO-based nanoparticles and a polymer, wherein the ZnO-based nanoparticles have a formula of Li x Mg y M p Zn z O, wherein 0≤x≤0.2; 0≤y+p≤0.25; z=1-0.5xy-1.5p; and M is an element selected from gallium and / or aluminum; and wherein the polymer comprises polyvinylpyrrolidone (PVP) and / or poly(ethyloxazoline) (PEO), the polymer having an average molecular weight M of 25000Da to 1300000Da w .

[0011] Another aspect of the present disclosure relates to a QLED, comprising the ETL according to the above aspect.

[0012] Another aspect of the present invention relates to a visual display unit, which comprises the QLED according to the above aspect. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 The measured external quantum efficiency of the QLED of Example 5 is shown.

[0014] Figure 2 The measured voltage of the QLED of Example 5 is shown. DETAILED DESCRIPTION

[0015] The present invention seeks to address at least some of the problems associated with the prior art or at least provide a commercially acceptable alternative solution thereto.

[0016] In a first aspect, the present invention provides a composition comprising ZnO-based nanoparticles, a polar organic solvent and a polymer.

[0017] The ZnO-based nanoparticles have the formula Li x Mg y M p Zn z O, where

[0018] 0≤x≤0.2;

[0019] 0≤y+p≤0.25;

[0020] z = 1 - 0.5xy - 1.5p; and

[0021] M is an element selected from gallium and / or aluminum; and

[0022] The polymer comprises polyvinyl pyrrolidone (PVP) and / or poly(ethyloxazoline) (PEO), and the polymer has an average molecular weight M of 25,000 to 1,300,000 Da. w .

[0023] Unless expressly indicated to the contrary, each aspect or embodiment as defined herein may be combined with any other aspect or embodiment. In particular, any feature indicated as being preferred or advantageous may be combined with any other feature indicated as being preferred or advantageous.

[0024] Through a series of experiments, the inventors of the present invention have surprisingly found that changing the average molecular weight of the polymer in the composition according to the present invention can have a significant effect on the EQE of a QLED comprising an ETL prepared using such a composition. The composition is typically a suspension, and the polymer can generally be referred to as a dispersant or stabilizer. Such terms are used interchangeably herein.

[0025] For example, as mentioned above, Heng Zhang et al. have studied the use of PVP as such a stabilizer. However, the effect of its molecular weight on stability and / or performance has not been studied.

[0026] The present inventors have surprisingly found that the average molecular weight M of 25000Da to 1300000Da w This can lead to a significant increase in the EQE performance of the composition in the resulting QLED.

[0027] Without being bound by theory, we believe that these unexpected effects may be due to the structure of the resulting layers that can be formed. For example, the filling of the layers of the resulting ETL can be improved. This can help achieve lower surface roughness in the ETL, which is desirable. For example, compared to QLEDs made using the compositions of the present invention, M<25000 Da is less than 25000 Da.w The inventors have found that increasing the M of the dispersant w The EQE of such QLEDs can be increased. However, if the polymer w If it is too high, the unexpected effect may not be observed or the effect may be reduced.

[0028] In addition to the beneficial effect on the EQE of the resulting QLED, the inventors have also found that the stability, i.e., shelf life, of the composition can be improved by using a specific stabilizer of the invention. Ideally, such a composition should be stable for several months. However, in the absence of such a stabilizer, the nanoparticles may fall off from the solvent, for example, after about three weeks.

[0029] In addition, the nanoparticles can have excellent dispersibility in the composition. Without being bound by theory, we believe that this may be due to favorable interactions with the specific polymers of the present invention, particularly the polymers in the solvents described herein. The composition is generally colorless or translucent, which is believed to be due to the excellent dispersibility of the nanoparticles in the composition. Therefore, the composition can allow the preparation of easily dispersible (doped) ZnO single particle size particles in polar solvents without the need for ultrasonic treatment.

[0030] It is also noted that if no stabilizer is present, the peak EQE may decrease after about 3 weeks. However, using the stabilizer of the present invention, the peak EQE can be stabilized for more than three months in the presence of the stabilizer.

[0031] It was also surprisingly found that similar to M w PEO of can also achieve almost the same or comparable stability and resulting EQE as PVP. Advantageously, both PVP and PEO are non-toxic.

[0032] As used herein, the term "nanoparticle" takes its usual meaning in the art. For example, a nanoparticle may be a particle having a diameter ranging from about 1 nm to 100 nm as measured by TEM.

[0033] As used herein, the term "ZnO-based nanoparticles" encompass nanoparticles comprising ZnO or doped ZnO. ZnO may be doped with lithium, magnesium, gallium and / or aluminum, for example. The ZnO-based nanoparticles have the formula Li x Mg y M p Zn zO, wherein 0≤x≤0.2; 0≤y+p≤0.25; z=1-0.5xy-1.5p; and M is an element selected from gallium and / or aluminum. The presence of Li is not required. However, a typical method for making such nanoparticles may involve the use of a lithium-based precursor. Therefore, residual lithium is typically present in ZnO-based nanoparticles. It should be understood that other methods that do not produce the presence of lithium may also be used. The effect of residual lithium on performance has not yet been determined. However, we believe that residual lithium has no significant effect on the performance of ZnO-based nanoparticles in ETL. If alternative precursors are used, other unavoidable trace elements may also be present in small amounts.

[0034] Preferably, the composition consists essentially of ZnO-based nanoparticles, a polar organic solvent, and a polymer, and more preferably consists of ZnO-based nanoparticles, a polar organic solvent, and a polymer.

[0035] As used herein, the term "consisting essentially of can encompass the possibility that certain other components besides those listed may be present, provided that they do not materially affect the basic characteristics of the composition.

[0036] The composition may be, for example, a precursor to an ETL for a QLED.

[0037] Preferably, the polymer is PVP and / or PEO.

[0038] As is known in the art, the average molecular weight M w Determined by the following molecular formula:

[0039]

[0040] Where N i is the molecular mass M i The number of molecules. w It can be measured using known techniques.

[0041] Preferably, the polymer has an M of 25000 Da to 500000 Da, more preferably 25000 Da to 200000 Da, still more preferably 25000 Da to 100,000 Da, but still more preferably 25000 Da to 75000 Da, but still more preferably 30000 Da to 70000 Da, more preferably 35000 Da to 70000 Da, but still more preferably 40000 Da to 65000 Da, even more preferably 45000 Da to 65000 Da, and even more preferably 50000 Da to 63000 Da. w Most preferably, the polymer M w As described herein, such molecular weights can result in particularly advantageous stability and enhanced EQE properties.

[0042] Preferably, the polymer comprises PVP. More preferably, the polymer is PVP. PVP can provide the best stability and enhanced EQE characteristics.

[0043] Preferably, p = 0 and y>0. In other words, the ZnO-based nanoparticles are preferably doped only with magnesium, and optionally lithium. ZnO doped with magnesium can produce the best performance in the ETL layer. In an alternative preferred embodiment, M is preferably aluminum. In another alternative preferred embodiment, y = 0 and p>0, preferably where M is aluminum. In other words, the ZnO-based nanoparticles are preferably doped only with aluminum and / or gallium, preferably aluminum, and optionally lithium.

[0044] In some embodiments, 0<x≤0.2, 0.01≤x≤0.2, 0.05≤x≤0.15, 0.08≤x≤0.12, or a range formed by any combination of these endpoints. The amount of lithium is not particularly limited and may depend on the manufacturing method.

[0045] Preferably, 0<y + p≤0.25, more preferably 0.01≤y + p≤0.25, more preferably 0.05≤y + p≤0.25, more preferably 0.10≤y + p≤0.20, even more preferably 0.15≤y + p≤0.20. Of course, it should be understood that, for example, if p = 0, then 0<y + p≤0.25 becomes 0<y≤0.25. In other words, such a chemical formula does not require both y and p to be non-zero. When used in the ETL layer, this amount of dopant (especially magnesium and / or aluminum) can produce the best EQE performance. The EQE of undoped ZnO nanoparticles is usually less than that of doped ZnO nanoparticles. Therefore, it is generally preferred that the ZnO-based nanoparticles are doped with magnesium and / or M, that is, preferably y + p>0.

[0046] One skilled in the art can select a suitable polar organic solvent. However, the polar organic solvent preferably includes ethanol, n-propanol, isopropanol, n-butanol, sec-butanol, tert-butanol, or a mixture of two or more of them, more preferably ethanol and / or isopropanol. Preferably, the polar organic solvent is ethanol and / or isopropanol. Most preferably, the solvent is ethanol. For example, ethanol can provide the most stable composition.

[0047] Preferably, the weight ratio of ZnO-based nanoparticles to polymer is 1:0.05 to 1:0.5, preferably 1:0.15 to 1:0.4, more preferably 1:0.3 to 1:0.4. It has been found that a higher weight percentage of the polymer (e.g., PVP) included in the composition can also improve the above-mentioned optimized properties. Without being bound by theory, it is believed that such a weight ratio can optimize, for example, the interaction between the polymer and the ZnO-based nanoparticles in the composition. For example, it may be particularly preferred if the total weight of PVP is about 30 weight % of the total weight of the ZnO-based nanoparticles in the composition.

[0048] Preferably, the composition comprises 0.1 wt % to 10 wt %, more preferably 0.5 wt % to 5 wt %, still more preferably 1 wt % to 4 wt %, even more preferably 2 wt % to 3 wt %, and most preferably about 2.5 wt % of ZnO-based nanoparticles based on the total weight of the polar organic solvent. For example, such a concentration of nanoparticles may be particularly suitable for a spin coating process to prepare an ETL.

[0049] Preferably, the ZnO-based nanoparticles have an average particle size of 1 nm to 20 nm, preferably 1 nm to 10 nm. This can be measured using TEM and / or SEM, for example using standard techniques. Therefore, the average particle size is typically the number average particle size, i.e. D[1,0]. The particle size distribution of the ZnO-based nanoparticles is preferably monodisperse. In other words, the ZnO-based nanoparticles are preferably substantially uniform in size, e.g. each particle has the same particle size within ±10%. Preferably, the average particle size is small so that the resulting ETL can be smooth, i.e. the surface roughness is low. Since the ETL is very thin, a small particle size may be required to obtain a smooth surface.

[0050] In another aspect of the present invention, there is provided a method for manufacturing an electron transport layer (ETL) for a QLED, the method comprising:

[0051] Providing a composition according to the first aspect;

[0052] spin coating the composition to provide a spin-coated composition; and

[0053] The spin-coated composition is annealed.

[0054] Typically, the polar organic solvent may be substantially evaporated during the formation of the ETL.

[0055] Suitable spin coating techniques are known in the art. For example, spin coating may include a procedure for depositing a uniform thin film onto a flat substrate. A small amount of coating material is usually applied to the center of a substrate that rotates at a low speed or does not rotate at all. The substrate is then rotated at a speed of up to 10,000 rpm to spread the coating material (and evaporate the solvent) by centrifugal force. The machine used for spin coating may be referred to as a spin coater, or simply as a spinner. For example, spin coating may involve spinning the composition at a speed of about 1000 rpm to about 3000 rpm (such as about 2000 rpm) for about 30 seconds to about 90 seconds (such as, for example, about 1 minute). Spin coating may also be referred to as centrifugal rubber mold casting. For example, the method utilizes inertia to produce castings from a rubber mold.

[0056] Suitable annealing techniques are known in the art. For example, annealing may involve annealing on a hot plate at about 80° C. to about 120° C. (such as about 100° C.) for, for example, about 5 minutes to about 15 minutes (such as, for example, about 10 minutes). Annealing the spin-coated composition typically forms an ETL, which can be incorporated into a QLED.

[0057] Alternatively, on a larger scale, inkjet printing can be used to manufacture ETLs using the compositions disclosed herein.

[0058] In another aspect of the present invention, there is provided use of the composition of the first aspect in the manufacture of an electron transport layer (ETL) for a QLED. Suitable techniques for using such a composition are known to those skilled in the art.

[0059] In another aspect of the present invention, an electron transport layer (ETL) for QLED is provided, the ETL comprising ZnO-based nanoparticles and a polymer, wherein the ZnO-based nanoparticles have a formula of Li x Mg y M p Zn z O, where

[0060] 0≤x≤0.2;

[0061] 0≤y+p≤0.25;

[0062] z = 1 - 0.5xy - 1.5p; and

[0063] M is an element selected from gallium and / or aluminum; and

[0064] The polymer comprises polyvinyl pyrrolidone (PVP) and / or poly(ethyloxazoline) (PEO), and the polymer has an average molecular weight M of 25,000 to 1,300,000 Da. w .

[0065] Preferred features and advantages described herein with reference to the first aspect apply equally to this aspect. It will be appreciated that the ETL of this aspect is, for example, the intended product of the precursor composition of the first aspect.

[0066] The ETL preferably has a surface roughness of 2 nm or less, for example, a surface roughness of 1.8 nm or less, 1.6 nm or less, 1.4 nm or less, or 1.2 nm or less. The surface roughness can be measured, for example, by atomic force microscopy. A smooth ETL is particularly preferred in QLED technology.

[0067] In another aspect of the present invention, there is provided a QLED comprising an ETL according to the above aspects. Such a QLED may demonstrate an improved EQE as described herein.

[0068] In another aspect of the present invention, a visual display unit is provided, the visual display unit comprising the QLED according to the above aspect.

[0069] The invention will now be described with reference to the following non-limiting examples.

[0070] Preparation of composition

[0071] The compositions according to the invention were prepared according to the following examples.

[0072] Example 1 - Preparation of Nanoparticles 15 mol % Mg-doped ZnO from Zn / Mg acetate / hexane

[0073] Zinc acetate dihydrate (0.012 mol, 2.63 g, Aldrich 99.999%) and magnesium acetate tetrahydrate (0.45 g, 15 mol%) were added to 120 ml of ethanol and refluxed for 2.5 hours to obtain a clear solution. The solution was then cooled to room temperature.

[0074] Lithium hydroxide (0.014 mole, 0.34 g) was then dissolved in 120 ml of ethanol and sonicated for about 15 minutes. This solution was then added to the zinc acetate / magnesium acetate tetrahydrate solution over 15 minutes while stirring vigorously. No significant changes occurred. It was then allowed to stir overnight (about 17 hours) at room temperature.

[0075] No significant changes occurred after this period.

[0076] Then 240 ml of the solution was mixed with 1000 ml of n-hexane to precipitate the Mg-doped ZnO to obtain a milky white solution. The precipitate was allowed to settle from the Mg-doped ZnO / ethanol / hexane dispersion for 2 hours and the supernatant was discharged. The remaining dispersion was placed in two 50 ml centrifuge tubes and centrifuged at 7000 rpm for 5 minutes. After decantation, the white product in the tube was rinsed with anhydrous ethanol (2 ml×2) and 25 ml of ethanol (dehydrated through molecular sieves) was added to obtain a 2.5 wt % dispersion. The test tube was stirred to disperse the product, and a clear solution was obtained in both cases. The solution was mixed and 1.8 ml of 10% PVP (M w =25000) ethanol solution.

[0077] The composition of ZnO-based nanoparticles is expected to be Li 0.07 Mg 0.15 Zn 0.815 O.

[0078] Example 2 - Preparation of Nanoparticles 10 mol% Mg-doped ZnO from Zn / Mg Acetate / Hexane

[0079] Zinc acetate dihydrate (0.01 mole, 2.195 g, Aldrich 99.999%) and magnesium acetate tetrahydrate (0.228 g, 10 mole%) were added to ethanol and refluxed for 2.5 hours to obtain a clear solution. The solution was then cooled to room temperature.

[0080] Lithium hydroxide (0.01 mole, 0.275 g) was then dissolved in 100 ml of ethanol and sonicated for about 15 minutes. This solution was then added to the zinc acetate / magnesium acetate tetrahydrate solution for more than 15 minutes while stirring vigorously. No significant changes occurred. It was then allowed to stir overnight (22.5 hours) at room temperature.

[0081] No significant changes occurred after this period.

[0082] The 200 ml solution was then mixed with 900 ml of n-hexane to precipitate the Mg-doped ZnO, resulting in a milky white solution. The precipitate was allowed to settle from the Mg-doped ZnO / ethanol / hexane dispersion for 2 hours, and the supernatant was removed. The remaining dispersion was placed in two 50 ml centrifuge tubes and centrifuged at 7000 rpm for 5 minutes. After decantation, the white product in the tube was rinsed with anhydrous ethanol (2 ml x 2) and ethanol (dehydrated by passing through molecular sieves) was added to obtain a 2.5 wt % dispersion. The test tube was stirred to disperse the product, and a clear solution was obtained in both cases. The solution was mixed, and PVP (M w =25000) and PVP(M w =58000):

[0083] Tube 1: 0.75 ml of 10% PVP 25000 / EtOH per 10 ml of nanoparticle dispersion

[0084] Tube 2: 0.75 ml of 10% PVP 58000 / EtOH per 10 ml of nanoparticle dispersion

[0085] The composition of ZnO-based nanoparticles is expected to be Li 0.07 Mg 0.1 Zn 0.865 O.

[0086] Example 3 - Preparation of Nanoparticles 5 mol % Al-doped ZnO from Zn / Acetate / Hexane

[0087] Zinc acetate dihydrate (0.01 mole, 2.195 g, 99.999% Sigma-Aldrich) and Al(acac)3 (0.172 g, 5 mole%) were added to 100 ml of ethanol. The solution was heated to boiling and the solid dissolved to give a clear solution.

[0088] After 2.5 hours, the solution was cooled. Then, a solution of lithium hydroxide (0.011 mol, 0.252 g) in 100 ml of ethanol was added over 10 minutes. The LiOH was dissolved in ethanol by ultrasonic treatment for 15 minutes beforehand. Then, it was stirred overnight for 16 hours.

[0089] Then 200 ml of the solution was made up with 900 ml of n-hexane to precipitate the Al-doped ZnO to obtain a milky white solution. The precipitate was allowed to settle from the Al-doped ZnO / ethanol / hexane dispersion for 2 hours and the supernatant was discharged. The remaining dispersion was placed in two 50 ml centrifuge tubes and centrifuged at 7000 rpm for 5 minutes. After decantation, the white product in the tube was rinsed with anhydrous ethanol (2 ml×2) and ethanol (dehydrated through molecular sieves) was added to obtain a 2.5 wt% dispersion. The test tube was stirred to disperse the product, and a clear solution was obtained in both cases. The solution was mixed and PVP (M w =58000):

[0090] Tube 1: 0.75 ml of 10% PVP 25000 / EtOH per 10 ml of nanoparticle dispersion

[0091] Tube 2: 0.75 ml of 10% PVP 58000 / EtOH per 10 ml of nanoparticle dispersion

[0092] The composition of ZnO-based nanoparticles is expected to be Li 0.07 Al 0.05 Zn 0.89 O.

[0093] Example 4 - Preparation of Nanoparticles 20 mol% Mg-doped ZnO from Zn / Mg Acetate / Hexane

[0094] Zinc acetate dihydrate (0.01 mole, 2.195 g, Aldrich 99.999%) and magnesium acetate tetrahydrate (0.536 g, 20 mole%) were added to ethanol and refluxed for 2.5 hours to obtain a clear solution. The solution was then cooled to room temperature.

[0095] Lithium hydroxide (0.011 mole, 0.299 g) was then dissolved in 100 ml of ethanol and sonicated for about 15 minutes. This solution was then added to the zinc acetate / magnesium acetate tetrahydrate solution over 15 minutes while stirring vigorously. No significant changes occurred. It was then allowed to stir overnight (22.5 hours) at room temperature.

[0096] No significant changes occurred after this period.

[0097] The 200 ml solution was then mixed with 900 ml of n-hexane to precipitate the Mg-doped ZnO, resulting in a milky white solution. The precipitate was allowed to settle from the Mg-doped ZnO / ethanol / hexane dispersion for 2 hours, and the supernatant was removed. The remaining dispersion was placed in two 50 ml centrifuge tubes and centrifuged at 7000 rpm for 5 minutes. After decantation, the white product in the tube was rinsed with anhydrous ethanol (2 ml x 2) and ethanol (dehydrated by passing through molecular sieves) was added to obtain a 2.5 wt % dispersion. The test tube was stirred to disperse the product, and a clear solution was obtained in both cases. The solution was mixed, and PVP (M w =25000) and PVP(M w =58000):

[0098] Tube 1: 0.75 ml of 10% PVP 25000 / EtOH per 10 ml of nanoparticle dispersion

[0099] Tube 2: 0.75 ml of 10% PVP 58000 / EtOH per 10 ml of nanoparticle dispersion

[0100] The composition of ZnO-based nanoparticles is expected to be Li 0.07 Mg 0.2 Zn 0.765 O.

[0101] QLED Testing

[0102] Example 5

[0103] Bottom-emitting red cadmium-free QLEDs were fabricated using Mg0.15 ZnO-based ETLs with different molecular weights of PVP and PEO as stabilizer polymers. The layer structure of the red QLED is as follows: Al (80nm); ~50-80nm ETL; ~15-20nm red cadmium-free QDs; 20nm hole transport layer (HTL); 40nm PEDOT:PSS (poly(3,4-ethylenedioxythiophene):poly(styrene-sulfonate)); 100nm indium tin oxide (ITO). The ETL of each QLED does not have PVP / PEO, M w 25000 PVP, M w 58000 PVP and M w 50000PEO.

[0104] Testing QLEDs and measuring peak EQE and 10mA / cm 2 The result is Figure 1 The peak EQE value is the higher value of each QLED, indicated by the square mark. 10mA / cm 2 The EQE below is the lower value for each QLED, indicated by the circular markers. The best EQE performance occurs at M w 58000PVP. The voltage was also measured under the same conditions. Figure 2 The voltages are shown to produce peak EQE and give 10 mA / cm 2 The so-called "driving voltage" of the current density.

[0105] Example 6

[0106] Red cadmium-free QLEDs were fabricated using different Mg or M dopants in ETL’s ZnO nanoparticles and also using different molecular weights of PVP.

[0107] Testing QLEDs and measuring peak EQE and 10mA / cm 2 The results are described in Table 1 below. The EQE values ​​are given to the nearest 1%. Magnesium, aluminum and gallium are used as dopants. M, y and p refer to the formula of the ZnO doped nanoparticles described herein. Due to the method of making the ETL, Li may be present in small amounts. The gallium-doped samples do not contain PVP / PEO. The voltage was also measured under the same conditions and the results are shown in Table 2. The voltage is given to the nearest 0.25V.

[0108]

[0109] Table 1

[0110]

[0111] Table 2

[0112] The dispersions with the highest EQE are Mg0.1ZnO(1367)+PVP 25k; Mg0.15ZnO+PVP 25k; Mg0.15ZnO+PVP 58k; Mg0.2ZnO+PVP 25k; Mg0.2ZnO+PVP 58k; and Al0.05ZnO+PVP 58k. Most of the driving voltages are below 5V.

[0113] The foregoing detailed description has been provided by way of explanation and illustration and is not intended to limit the scope of the appended claims. Many variations of the presently preferred embodiments shown herein will be apparent to those of ordinary skill in the art and remain within the scope of the appended claims and their equivalents.

Claims

1. A composition, the composition comprising ZnO-based nanoparticles, a polar organic solvent, and a polymer, The ZnO-based nanoparticles have the formula Li x Mg y M p Zn z O, where 0≤x≤0.2; 0 ≤ y + p ≤ 0.25; z = 1 - 0.5x - y - 1.5p; and M is an element selected from gallium and / or aluminum; and The polymer comprises polyvinyl pyrrolidone (PVP) and / or poly(ethyloxazoline) (PEO), and the polymer has an average molecular weight M of 25000 Da to 1300000 Da. w .

2. The composition according to claim 1, wherein the polymer has a molecular weight of 25000Da to 200000Da, preferably 25000Da to 100000Da, more preferably 30000Da to 70000Da. w .

3. A composition according to claim 1 or claim 2, wherein the polymer has a M of 45000Da to 65000Da. w .

4. The composition according to any one of the preceding claims, wherein the polymer comprises PVP.

5. The composition according to any one of the preceding claims, p = 0 and y > 0.

6. The composition according to any one of claims 1 to 4, wherein y = 0 and p > 0, preferably wherein M is aluminum.

7. The composition according to any one of the preceding claims, wherein 0.05 ≤ y + p ≤ 0.25, preferably wherein 0.10 ≤ y + p ≤ 0.20, more preferably 0.15 ≤ y + p ≤ 0.

20.

8. The composition according to any one of the preceding claims, wherein the polar organic solvent comprises ethanol, n-propanol, isopropanol, n-butanol, sec-butanol, tert-butanol, or a mixture of two or more thereof, preferably ethanol and / or isopropanol.

9. The composition according to any one of the preceding claims, wherein the weight ratio of ZnO-based nanoparticles to the polymer is 1:0.05 to 1:0.5, preferably 1:0.15 to 1:0.4, more preferably 1:0.3 to 1:0.

4.

10. The composition according to any one of the preceding claims, wherein the composition comprises 0.1% by weight to 10% by weight of ZnO-based nanoparticles based on the total weight of the polar organic solvent.

11. The composition according to any one of the preceding claims, wherein the ZnO-based nanoparticles have an average particle size of 1 nm to 20 nm, preferably 1 nm to 10 nm.

12. The composition according to any one of the preceding claims, wherein 0 < x ≤ 0.2, and preferably 0.01 ≤ x ≤ 0.

2.

13. A method of manufacturing an electron transport layer (ETL) for a quantum dot light emitting diode (QLED), the method comprising: providing the composition according to any one of claims 1 to 12; spin-coating the composition to provide a spin-coated composition; and annealing the spin-coated composition.

14. Use of the composition according to any one of claims 1 to 12 in manufacturing an electron transport layer (ETL) for a QLED.

15. An electron transport layer (ETL) for QLED, the ETL comprising ZnO-based nanoparticles and a polymer, wherein the ZnO-based nanoparticles have a formula of Li x Mg y M p Zn z O, where 0≤x≤0.2; 0 ≤ y + p ≤ 0.25; z = 1 - 0.5x - y - 1.5p; and M is an element selected from gallium and / or aluminum; and The polymer comprises polyvinyl pyrrolidone (PVP) and / or poly(ethyloxazoline) (PEO), and the polymer has an average molecular weight M of 25000 Da to 1300000 Da. w .

16. The ETL according to claim 15, wherein the polymer has an M of 25000Da to 200000Da, preferably 25000Da to 100000Da, more preferably 30000Da to 70000Da. w .

17. The ETL of claim 15 or claim 16, wherein the polymer has an M of 45,000 to 65,000 Da. w .

18. The ETL according to any one of claims 15 to 17, wherein the polymer comprises PVP.

19. The ETL according to any one of claims 15 to 18, wherein p = 0 and y > 0.

20. The ETL according to any one of claims 15 to 18, wherein y = 0 and p > 0, preferably wherein M is aluminum.

21. The ETL according to any one of claims 15 to 20, wherein 0.05 ≤ y + p ≤ 0.25, preferably wherein 0.10 ≤ y + p ≤ 0.20, more preferably 0.15 ≤ y + p ≤ 0.

20.

22. The ETL according to any one of claims 15 to 21, wherein the weight ratio of ZnO-based nanoparticles to polymer is from 1:0.05 to 1:0.5, preferably from 1:0.15 to 1:0.4, more preferably from 1:0.3 to 1:0.

4.

23. The ETL according to any one of claims 15 to 22, wherein the ZnO-based nanoparticles have an average particle size of 1 nm to 20 nm, preferably 1 nm to 10 nm.

24. A QLED comprising the ETL according to any one of claims 15 to 23.

25. A visual display unit comprising the QLED according to claim 24.